Forest Entomology and Pathology Volume 1: Entomology - D. Allison, Jeremy; Paine, Timothy D.; Slippers, Bernard; Wingfield, Michael J. (Springer Nature, 2023)
This open access book will provide an introduction to forest entomology, the principles and techniques of forest insect pest management, the different forest insect guilds/feeding groups, and relevant forest insect pest management case studies. In addition to covering 30% of the earth, forest ecosystems provide numerous timber and non-timber products that affect our daily lives and recreational opportunities, habitat for diverse animal communities, watershed protection, play critical roles in the water cycle, and mitigate soil erosion and global warming. In addition to being the most abundant organisms in forest ecosystems, insects perform numerous functions in forests, many of which are beneficial and critical to forest health. Conversely, some insects damage and/or kill trees and reduce the capacity of forests to provide desired ecosystem services. The target audience of this book is upper-level undergraduate and graduate students and professionals interested in forest health and entomology. ; A comprehensive companion textbook for undergraduate and graduate courses in Forest Entomology has not been published since the text by Coulson and Witter in 1984. Comprehensive case studies to accompany chapters on specific feeding guilds and pest management. This text will have a chapter addressing the invasion biology of forest insects. This text will have a companion volume co-edited by the same four editors (Volume 1: Allison, Paine, Slippers and Wingfield; Volume 2: Slippers, Wingfield, Paine and Allison).